Effect of eight weeks of wrestling and circuit fitness training on apo lipoprotein A-I and lymphocyte ABCA1 gene expression in well-trained wrestlers - Rashidlamir, A.; Saadatnia, A.; Ebrahimi-Atri, A.; Delphan, M. (International Journal of Wrestling Science, 2011)
Introduction: Atherosclerotic cardiovascular disease is now the leading cause of death in most countries. The ABCA1 gene provides instructions for the production of proteins (ATP-binding transporter protein) whose function is to export phospholipid and cholesterol out of the cells where they are bound to circulating apolipoprotein A1 (apoA1) and removed in the liver. Increased ABCA1 activity could inhibit atherosclerosis. In the present study, ABCA1 gene expression in lymphocytes and the associated effect of exercise were studied. Method: Subjects were 16 well-trained wrestlers randomly assigned into experimental and control groups. The experimental group performed 8 weeks of wrestling and circuit fitness training and the control group remained sedentary. Blood samples were collected 48 hours before the first session and 48 hours after the last session (subjects were fasting). After isolating lymphocytes by centrifugation, ABCA1 gene expression in lymphocytes was measured using semi-quantitative-RT-PCR. Data analyzed by SPSS software (version 16). Results: a significant increase in lymphocyte ABCA1 gene expression was shown following the 8 weeks of training (experimental p<0.001, t=-9.954). Plasma HDL-C concentrations and Apo A-I increased (P<0.001, t=4.97 P<0.05, t=2.67 respectively) and plasma LDL-C concentration decreased (P<0.001, t=4.35) in experimental group when compared with the control group. Discussion and Conclusion: Anaerobic exercises like wrestling and circuit fitness training can increase ABCA1 gene expression, an effective factor in the prevention of cardiovascular disease.